2020
DOI: 10.3390/ma13061376
|View full text |Cite
|
Sign up to set email alerts
|

Color Shift, Color Stability, and Post-Polishing Surface Roughness of Esthetic Resin Composites

Abstract: The aim of this study was to compare color shift, color stability, and post-polishing surface roughness of esthetic restorative materials. Twenty-five disc-shaped specimens (10 mm in diameter and 2 mm in thickness) from five esthetic resin materials (Z250XT, IPS Empress-Direct, G-ænial, Vit-l-escence, and Ceram.X) were fabricated. Color shift before and immediately after light-curing (∆E0) then color stability after immersion in tea, coffee, berry juice, and distilled water were measured using a spectrophotome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 39 publications
3
40
0
9
Order By: Relevance
“…The optical properties of composite resins change based on the photopolymerization received, and the extent of change is affected by the characteristics of the material and the wavelength emitted by the polymerizing unit. 4 , 10 , 11 In the present study, both the material and the light-emitting source were standardized so that these variables would not interfere with the results, providing a proper assessment of the post-curing effect. Further studies should be performed to analyze the effect of these variations, especially with new materials and light-emitting sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optical properties of composite resins change based on the photopolymerization received, and the extent of change is affected by the characteristics of the material and the wavelength emitted by the polymerizing unit. 4 , 10 , 11 In the present study, both the material and the light-emitting source were standardized so that these variables would not interfere with the results, providing a proper assessment of the post-curing effect. Further studies should be performed to analyze the effect of these variations, especially with new materials and light-emitting sources.…”
Section: Discussionmentioning
confidence: 99%
“…The first factor might be the material selected because the nanofilled composite resin tested in the present study has shown high staining ability. 3 , 10 Another factor that might have contributed to the great color change was the inclusion of daily coffee immersions, with a high staining ability on the composite resin. 10 Coffee contains many ingredients, among which there is a considerable amount of hydrosoluble dyes and acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color stability can be assessed by instrumental and visual methods. The used Spectrophotometry in this study has proven to be a sound method in composite resins research, being capable of suppressing the individual analysis of visible color comparison [ 29 ]. All tested composite resins showed similar measurements of color change (∆E) during the 7 days except for HE-EC3 and HE-EC4 ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Color modification is a major reason for changing composite restorations, especially in the anterior region. Color stability of composite restorations is necessary to mimic and preserve the appearance of natural teeth and to satisfy patients' demands [3].…”
Section: Introductionmentioning
confidence: 99%